Application of Reverse Engineering on Spacecraft Assembly Process Simulation. (January 2020) - Yiliu, Xu; Chunsheng, Yang; Kai, Xu; Wei, Wang; Xing, Fan; Jun, Hou
Abstract: This paper proposes a new process that assembly simulation with 3-D model which obtained from product to improve the reliability of spacecraft assembly. 3-D model of the satellite camera which obtained by reverse engineering was used in DELMIA virtual assembly simulation. The point cloud date of the model was scanned by laser radar, and the scanning accuracy is 0.3mm. To get more accurate model data, firstly it's necessary to remove noise data by the method of HCI and curve inspect; then, min-distance method was used to streamline the point data, and repair the data by complementary surface; finally, reconstruct the model by the triangular Bezier surface. Because the model obtained by RE is more exact than the ordinary model, the virtual assembly simulation is more useful. During the period of installing the camera, as the simulation, the risk was avoided and the process was successful.